Paulo Freire and Guarulhos: popular education as a connection (Práxis Educativa, 2021)
In this article, we propose a discussion and a recording of Paulo Freire’s passage through the city of Guarulhos, a municipality in the metropolitan region of São Paulo, Brazil, in the 1980s, right after his exile. We analyze the author’s influence on the pedagogical conception of the Guarulhos education network, especially in in the Youth and Adult Education modality, at the Movement for the Valorization of Literacy (Movimento de Valorização da Alfabetização – MOVA). The hypothesis is that there is an attempt by the city to build a history of the network based on the figure of Paulo Freire. We start from the method of document analysis of the Almanaque MOVA 10 anos, published by the Municipal Education Department of Guarulhos, in 2012, in commemoration of the movement’s anniversary. In it we were able to find elements that endorse the articulation with Freire’s theory and perceive the adoption of these concepts by the management of the time, as well as the relationship that was established between the public power and the popular movement.Keywords: Paulo Freire. MOVA. Youth and Adult Education.